Relative Tense without Existential Quantification and Before. (21st October 2022) - Ogihara, Toshiyuki
Abstract: This article discusses the semantics of tense morphemes in Japanese in temporal adverbial clauses as well as in relative clauses. We claim that they are non-pronominal higher order entities but do not carry existential quantifier meanings on their own. Specifically, we argue against the view that Japanese past tense sentences are necessarily existentially quantifying and that this is the reason why they cannot occur as mae 'before' clauses. This view is incompatible with the fact that Japanese ato 'after' clauses must occur in the past tense. By contrast, our own proposal about Japanese tense morphemes is based on the idea that the inherent meaning of 'before' (or 'after') agrees with the "relative" meaning of the tense morpheme in the temporal adverbial clause. That is, a 'before' clause must be in the future tense (conveyed by the non-past tense form) because it describes a situation that follows the matrix predication time, whereas an 'after' clause must be in the past tense because it describes a situation that precedes the matrix predication time. Choosing the wrong tense form would then result in a contradiction. We will make two separate compositional proposals within two major accounts of 'before' and 'after': Beaver and Condoravdi's and Anscombe's. This enables us to show that correct empirical predictions can be made about 'before' and 'after' clauses, including non-veridical 'before' clauses, regardless of which account of temporal connectives turns out to be optimal. Our proposal also covers 'when' clauses and (nominal) relative clauses. Japanese tense morphemes are higher order entities and are "quantifier-raised" to yield "simultaneous readings" for present tense relative clauses. From the viewpoint of natural language semantic theory, this article establishes that non-pronominal relative tense morphemes are not always existentially quantifying. When an existential quantifier interpretation is needed, it is supplied through independent means. This is a promising approach to the semantics of relative-tense languages such as Japanese.